Edukasi Digital Parenting Islami Bagi Orang Tua: Upaya Manajemen Penggunaan Gadget Anak di Lingkungan Keluarga Muhammadiyah - Bayu Dwi Cahyono; Istianah (Jurnal Inovasi dan Pengabdian, 2026)
The rapid increase in gadget use during the Covid-19 pandemic has had numerous impacts on users, with the most vulnerable target being gadget addiction in children. Childhood is a crucial period for cognitive, motor, and social development. Socialization and mentoring of Islamic digital parenting education for parents as an effort to manage children's gadget use within the Muhammadiyah family environment, especially in Kembaran District, Banyumas Regency, is a concrete effort to overcome uncontrolled gadget addiction in children. This activity aims to provide education and mentoring to parents in assisting children to be able to use gadgets appropriately. The method used in implementing this activity is a participatory approach. Partners will be actively involved in every stage and activity that will be carried out through counseling, discussions, and joint practices. The final results of the author's educational efforts show positive results, including: increased parental understanding of the importance of supervising children's gadget use, increased parental technical skills in using applications for monitoring and controlling children's gadgets, and changes in parental attitudes in responding to children's behavior.